Alpha tocopherol transfer protein (αTTP) is expressed in endometrial carcinoma and is correlated with FIGO stage and 5-year survival - Heublein, Sabine; Faigle, Gesine (Journal of cancer research and clinical oncology, 2017)
Background: Increased oxidative stress plays an important role in cancer development. Vitamin E is considered a potent anti-oxidant and its transfer protein αTTP facilitates its cellular delivery. We hypothesize that αTTP could be present in and have an impact on endometrial cancer. Materials and methods: Ishikawa endometrial cancer cells were treated with BSO and AAPH to mimick oxidative stress conditions. αTTP was detected by immunocytochemistry and western blot. αΤΤP expression was then assessed in 191 endometrioid endometrial carcinomas. Immunopositivity was correlated with grade, FIGO stage, and 5-year survival. Immuno-reactivity was assessed with a semi-quantitative score. Results: AAPH- and BSO-induced αTTP expression in Ishikawa cells. Immunohistochemical assessment of the 191 endometrial cancer cases showed that αTTP expression correlated with FIGO stage (p = 0.014) but not with grade. Five-year survival was significantly better in cases of lower αTTP expression compared to cases with higher expression (p = 0.041). Conclusions: The current results show that αTTP plays a role in endometrial carcinoma. Possibly endometrial cancer cells attempt to protect themselves from increasing oxidative stress by up-regulating αTTP. Selective molecular interventions targeting oxidative stress escape strategies, e.g., by overexpression of αTTP, could, therefore, allow oxidative stress to damage cancer cell membranes and thus restrict cancer progression.